2017
DOI: 10.1037/adb0000285
|View full text |Cite
|
Sign up to set email alerts
|

Peer alcohol behavior moderates within-level associations between posttraumatic stress disorder symptoms and alcohol use in college students.

Abstract: Self-medication theory (SMT) posits that individuals exposed to trauma and resulting posttraumatic stress symptoms (PTSD) are at risk for heavy drinking and associated negative consequences. Close peer alcohol use is also a powerful predictor of alcohol involvement in college, particularly influencing those with greater negative affect. As individuals with PTSD may rely on peers for support, peer drinking behaviors are possibly putting them at further risk for greater alcohol use and resulting consequences. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…First, in a college environment, higher levels of social support from friends in particular may maintain substance use coping behaviors, which could prevent recovery from PTSD. Although some college students report drinking alone (Christiansen et al, 2002) and loneliness has been associated with substance use (Åkerlind and Hörnquist, 1992; Stickley et al, 2014), most college students who drink endorse drinking in social situations (Christiansen et al, 2002), and research suggests that peers influence drinking behavior among college students with PTSD specifically (Bachrach and Read, 2017). Thus, SA survivors with more social support from their friends may have more opportunities to use substances to cope, or may receive more support involving encouragement to do so.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, in a college environment, higher levels of social support from friends in particular may maintain substance use coping behaviors, which could prevent recovery from PTSD. Although some college students report drinking alone (Christiansen et al, 2002) and loneliness has been associated with substance use (Åkerlind and Hörnquist, 1992; Stickley et al, 2014), most college students who drink endorse drinking in social situations (Christiansen et al, 2002), and research suggests that peers influence drinking behavior among college students with PTSD specifically (Bachrach and Read, 2017). Thus, SA survivors with more social support from their friends may have more opportunities to use substances to cope, or may receive more support involving encouragement to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is evidence that perceived and received social support are associated with substance use in young trauma-exposed adults (Bachrach and Read, 2017; Gros et al, 2016). A study of young veterans with PTSD and a substance use disorder identified a positive association between alcohol use and perceived social support, and the authors explained that this finding might be explained by the high frequency of drinking in this population (Gros et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The present paper provides evidence that with some consideration, S-GIMME can be applied to ambulatory assessment data, of which daily diary data is a specific type. Here, daily diaries were specifically chosen because (a) they are an oft used variant of ambulatory assessment both historically (e.g., Borkenau & Orstendorf, 1998;Lebo & Nesselroade, 1978;Searles, Perrine, Mundt, & Helzer, 1995;Zevon & Tellegen, 1982) and at present (e.g., Bachrach & Read, 2017;Castro-Schilo & Ferrer, 2016;Gadassi et al, 2016;Hamaker, Grasman, & Kamphuis, 2016;Lee et al, 2017;Zimmermann et al, in press), and (b) the sampling rate is sometimes conducted at relatively equal spacing, an advantageous feature for time-series data in the current modeling context 1 . Nevertheless, application to daily diary data presents novel analytic concerns which may be absent in neuroimaging data.…”
mentioning
confidence: 99%
“…Thus, relationships not originally significant (e.g., income loss and coping motives; coping motives and solitary drinking) may become so over time. Third, other psychopathology besides depression and health anxiety are related to increased alcohol use and problems, such as social anxiety disorder, posttraumatic stress disorder, and personality pathology (Bachrach and Read, 2017; Creswell et al, 2016; Grant et al, 2005). Modeling a broader range of this pathology and changes in symptoms over time may reveal pathways to both coping motives and unhealthy alcohol use for individuals who are most vulnerable.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%